Analisis Strategi Pemasaran Untuk Meningkatkan Volume Penjualan Pada Toko Emas Anak Rokan Di Kecamatan Kubu Babussalam Kabupaten Rokan Hilir Dalam Ekonomi Islam - Zulfikar, Zulfikar; Desriani, Desriani; Wahyudi, Denny (Journal of Islamic Banking, Economics and Finance, 2024)
This research was conducted to see the increase in gold sales at Anak Rokan gold shops in Kubu Babussalam Rokan Hilir District and what strategies are used to increase sales volume and what, from an Islamic perspective, are the marketing strategies used at Anak Rokan gold shops. The research method used in this research is a qualitative method by conducting interviews with customers or buyers who shop at the Emas Anak Rokan store. Based on the results of the IE matrix analysis, Anak Rokan Gold Shop occupies Cell V, which means that the company or Gold Shop tends to carry out market penetration strategies and product development strategies. Based on the results of the Grand Strategy Matrix analysis, the Anak Rokan Gold Shop is located in quadrant 1, because according to the EFE and IFE, the opportunities for strength are greater than the threats and weaknesses. Anak Rokan Gold Shop must be more dominant in carrying out strategies by growing and developing products.